2021
DOI: 10.1016/j.ajem.2020.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Burnout amongst emergency healthcare workers during the COVID-19 pandemic: A multi-center study

Abstract: Burnout is a major healthcare issue [1] which has intensified with additional stressors arising from the ongoing 2019 Novel Coronavirus (COVID-19) pandemic [2,3]. Emergency Department (ED) healthcare workers (HCWs) have had one of the highest incidences of burnout [4][5][6] even prior to the pandemic. Being at the frontline in direct contact with patients suspected or confirmed to have a COVID-19 infection exacerbates this [7].To evaluate the prevalence of burnout in this population and the preferred methods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
139
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(170 citation statements)
references
References 15 publications
11
139
1
1
Order By: Relevance
“…After the screening of the titles and abstracts, we removed 191 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40] in this systematic review that met our inclusion criteria and among them six studies in the meta-analysis that included the appropriate data.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After the screening of the titles and abstracts, we removed 191 records and we added 4 more records found by the reference lists scanning. Finally, we included 14 studies [27][28][29][30][31][32][33][34][35][36][37][38][39][40] in this systematic review that met our inclusion criteria and among them six studies in the meta-analysis that included the appropriate data.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Main characteristics of the 14 studies included in our systematic review are shown in Table 1. Study population included only nurses in five studies, 27,28,33,36,40 while nine studies [29][30][31][32]34,35,[37][38][39] included HCWs in general. A total of 17,390 nurses were included in this systematic review, while two studies 37,38 did not report the number of nurses.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations